2018
DOI: 10.1073/pnas.1717044115
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a zosuquidar and UIC2-bound human-mouse chimeric ABCB1

Abstract: SignificanceThe ATP binding cassette transporter ABCB1 (also termed P-glycoprotein) is a physiologically essential multidrug efflux transporter of key relevance to biomedicine. Here, we report the conformational trapping and structural analysis of ABCB1 in complex with the antigen-binding fragment of UIC2, a human ABCB1-specific inhibitory antibody, and zosuquidar, a third-generation ABCB1 inhibitor. The structures outline key features underlining specific ABCB1 inhibition by antibodies and small molecules, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
209
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(225 citation statements)
references
References 68 publications
15
209
1
Order By: Relevance
“…Intriguingly, a cryo-EM structure of the mouse P-gp-ZDR complex was recently reported. 43 Through structural alignment, we observe that the experimentally determined protein structure is very similar to our simulated structure at the local minimum of Z…”
Section: Connection Of Statistically Averaged Microscopic Events Tosupporting
confidence: 52%
“…Intriguingly, a cryo-EM structure of the mouse P-gp-ZDR complex was recently reported. 43 Through structural alignment, we observe that the experimentally determined protein structure is very similar to our simulated structure at the local minimum of Z…”
Section: Connection Of Statistically Averaged Microscopic Events Tosupporting
confidence: 52%
“…The strategy of generating state-specific binders against type I ABC exporters has a long history going back to the 90's of the last century, when the state-specific ABCB1 antibody UIC2 was identified 17 . A recent cryo-EM structure of UIC2 in complex with ABCB1 revealed that the antibody clamps the extracellular loops together, thereby preventing extracellular gate opening 18 . Molecular clamping of the closed extracellular gate was also achieved by a cyclic peptide raised against CmABCB1 19 .…”
Section: Discussionmentioning
confidence: 99%
“…A Fourier shell correlation value of 0.143 was reached at 7.9Å. The structural data obtained was therefore at lower resolution than was possible by cross-linking and extensive mutagenesis of the protein (6,13); however it was at higher resolution than data previously obtained by cryo-EM for active P-gp in the presence of a stabilising antibody fragment (14). Flexibility may be a prerequisite for active protein, hence may be an intrinsic limitation to structural studies of single particles where there are no constraints due to a crystal lattice.…”
Section: Resultsmentioning
confidence: 91%
“…Compared to the map presented in Figure 3, the cavity for Zosuquidar appears to be slightly smallerperhaps because of the cross-linking of the NBDs or the addition of the UIC2 antibody. These factors may have forced a narrower angle to be subtended between the two TMDs in the Zosuquidar study (13). Similarly, a study of Pglycoprotein with cyclic peptides designed to probe the allocrite-binding pocket showed two molecules bound in the same locations as in Figure 3.…”
Section: Drug Binding Sites (Purple Density)mentioning
confidence: 99%
See 1 more Smart Citation